Roma & Sinti Culture as Modern German Studies - Arushi Nair (Central Europe)
How can we spotlight the second generation of Roma & Sinti in the German speaking world? When the Roma are discussed or invited to speak, it is typically limited to their experience with the atrocities of World War Two, and so their voices become narrowly contextualized before the backdrop of a history of persecution, especially during the Holocaust. Seldom is the attention on their culture and their own history. In a shift to focus on the art, poetry and literature of the Roma, I am hoping to empower the voices within the second generation, all those born in an era disconnected from the war. I argue  that these perspectives are invaluable to the discipline of German Studies and that there is much more to this group than the discrimination and pain they have faced. Although the injustices of past and present have indeed been formative in the lives of so many Roma & Sinti, it limits the scope of what we know and can learn from them.